2010
DOI: 10.1111/j.1399-3054.2010.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of microRNA in Arabidopsis in response to phosphate starvation as studied by locked nucleic acid-based microarrays

Abstract: MicroRNAs (miRNAs) are short RNA chains (20-24 bp) which are emerging as important regulators of gene expression. miRNAs are encoded by specific genes, and in Arabidopsis, 190 genes have presently been identified. It has been shown that miR399 is essential for the phosphate starvation response, and recent studies have shown transcriptional changes in a number of additional miRNAs in response to a shortage of phosphate. In this study, global profiles of the miRNA in shoots of Arabidopsis plants grown on limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 35 publications
3
41
1
1
Order By: Relevance
“…We confirmed that the well-studied miR399 and miR827 were both upregulated by phosphate starvation, as reported previously in Arabidopsis (Fujii et al, 2005;Aung et al, 2006;Chiou et al, 2006;Hsieh et al, 2009;Pant et al, 2009;Lundmark et al, 2010) and in rice (Bari et al, 2006;Lin et al, 2010). Intriguingly, miR827 was also strongly induced by the combined stress of salt stress under conditions of potassium starvation ( Figure 6G).…”
Section: Environmental Stress-associated Mirnas and Their Targetssupporting
confidence: 91%
See 2 more Smart Citations
“…We confirmed that the well-studied miR399 and miR827 were both upregulated by phosphate starvation, as reported previously in Arabidopsis (Fujii et al, 2005;Aung et al, 2006;Chiou et al, 2006;Hsieh et al, 2009;Pant et al, 2009;Lundmark et al, 2010) and in rice (Bari et al, 2006;Lin et al, 2010). Intriguingly, miR827 was also strongly induced by the combined stress of salt stress under conditions of potassium starvation ( Figure 6G).…”
Section: Environmental Stress-associated Mirnas and Their Targetssupporting
confidence: 91%
“…Perhaps the most well-studied miRNAs that are regulated by and function during environmental stress are miR399 and miR827, both of which are induced by phosphate starvation (Fujii et al, 2005;Aung et al, 2006;Bari et al, 2006;Chiou et al, 2006;Duan et al, 2008;Pant et al, 2009;Lin et al, 2010;Lundmark et al, 2010;Kant et al, 2011). Our study confirmed this regulation ( Figure 6E) as well as the sulfur starvation induction of miR395 (Jones- ) that, to our knowledge, prior to this work had not been reported in rice.…”
Section: Environmental Stress-regulated Mirnassupporting
confidence: 85%
See 1 more Smart Citation
“…Members of the IPSI1/Mt4/At4 family of noncoding transcripts, whose expression is rapidly and specifically induced in response to P starvation, appear to bind and sequester miR399s, thereby attenuating miR399-mediated transcriptional responses to P starvation (Franco-Zorrilla et al, 2007). In addition to miR399, several other microRNA species have been implicated in regulating plant responses to low P availability (Hsieh et al, 2009;Pant et al, 2009;Gu et al, 2010;Lin et al, 2010;Lundmark et al, 2010;Zhu et al, 2010). These include miR156, miR158, miR163, miR319, miR391, miR447, miR778, miR827, miR866, and miR2111, which increase in abundance in plants during P starvation.…”
Section: P Signaling Pathwaysmentioning
confidence: 99%
“…The microRNA169 (miR169) family is known to be regulated by both N and P starvation (Pant et al, 2009;Lundmark et al, 2010;Xu et al, 2011Xu et al, , 2013Zhao et al, 2011;Liang et al, 2012). Different members of this microRNA family show distinct response patterns to N or P starvation (Pant et al, 2009;Liang et al, 2012;Xu et al, 2013).…”
mentioning
confidence: 99%